Portable greenhouse / Ahmad Syukri Abdul Aziz - Abdul Aziz, Ahmad Syukri; Mohd Suhaimi, Ahmad Wafi; Alluwi, Ahmad Shahrizal; Mohd, Ahmad Alif Qadri (2018)
Observation and market research indicates that many people would love to plant. However, they do not plant because they do not have the time to take care of the plant. So the team have chosen Portable Greenhouse as a product to counter the problem.